A era Merkel e a hegemonia europeia: ensaio sobre a dinâmica de poder no velho mundo - João Paulo Rodrigues Barros (2023)
The reunification of Germany after the fall of the Berlin Wall and the Merkel Era played a crucial role in the power dynamics in Europe, with significant impacts both within the European Union and globally. The adoption of the euro, the global financial crisis of 2008, and the formation of new strategic alliances and partnerships were strongly influenced by German hegemony, shaping the global geopolitical landscape in recent years. During the Merkel Era, which spanned from 2005 to 2021, Germany assumed a central role on the continent. The dissertation investigates the power dynamics within the bloc and how the Bundesrepublik Deutschland exerted its influence on European integration. The analysis of German policies and practices revealed how the country shaped EU decisions and influenced other countries, blocs, and institutions. This new German hegemony brought challenges to Europe, necessitating reflection on its future functioning and structure. Different visions were explored: a Europe dominated by Germany, as well as perspectives on cohesion and political development within the European community. Additionally, the influence of the North Atlantic, particularly the United States, also played a prominent role in continental affairs. This analysis is essential to understand the implications of the Merkel Era, which highlighted the relevance of Germany in the contemporary European scenario and emphasized its role in political architectures and the exercise of power, both within and beyond the European Union.